A Polymeric Composite Material (rGO/PANI) for Acid Blue 129 Adsorption - Kukulski, Tomasz; Wacławek, Stanisław; Silvestri, Daniele; Krawczyk, Kamil; Padil, Vinod V T; Fryczkowski, Ryszard; Janicki, Jarosław; Černík, Miroslav (Polymers, 2020)
Over the years, polyaniline (PANI) has received enormous attention due to its unique properties. Herein, it was chosen to develop a new polymeric composite material: reduced graphene oxide/polyaniline (rGO/PANI). The composite was prepared by a simple and cost-effective fabrication method of formation by mixing and sonication in various conditions. The obtained materials were characterized and identified using various techniques such as scanning electron microscopy (SEM), Raman and ATR-FTIR spectroscopy, and X-ray diffraction (XRD). The objective of the paper was to confirm its applicability for the removal of contaminants from water. Water could be contaminated by various types of pollutants, e.g., inorganics, heavy metals, and many other industrial compounds, including dyes. We confirmed that the Acid Blue 129 dyes can be substantially removed through adsorption on prepared rGO/PANI. The adsorption kinetic data were modeled using the pseudo-first-order and pseudo-second-order models and the adsorption isotherm model was identified.
Keywords: nanocomposite; Acid Blue 129; graphene; adsorption